Hubungan Bayi Berat Lahir Rendah dengan Kejadian Asfiksia di Rumah Sakit Roemani Muhammadiyah Semarang - Sintiya Sintiya; Kurnia Wijayanti; Indra Tri Astuti (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Asphyxia nonatorum contributed 30.3% to the cause of neonatal death in Central Java Province in 2019, in the case of LBW the percentage was greater than asphyxia neonatoum in cases of neonatal death in Central Java in 2019, namely 46.4%. This research design is quantitative research, with a cross-sectional approach. The sampling technique used the chi-square formula and obtained a sample of 40 respondents. The data collection method used data from medical records. Data analysis used univariate analysis and bivariate analysis using the chi-square test. The characteristics of the respondents were mostly male with a total of 26 babies (65.0%), the majority of the gestational age of the babies in the premature category was 25 people (62.5%). The majority of the babies' mothers had a high school education of 29 people (72.5%), the majority were born by CS procedure of 33 babies (82.5%), with normal amniotic fluid characteristics of 25 people (62.5%). The majority of babies had a weight in There were 22 babies (55.0%) in the LBW category, and the majority of respondents had LBW and moderate asphyxia, 12 babies (54.5%). Based on the analysis results, the d value was 0.518, indicating a moderate positive correlation with a p value (0.000 < 0.05), indicating a relationship between low birth weight and asphyxia at Roemani Muhammadiyah Hospital, Semarang. There is a relationship between low birth weight and asphyxia at Roemani Muhammadiyah Hospital, Semarang.